Implementasi Kebijakan Pengembangan Pariwisata Pasca Pandemic di Indonesia - Ihin Solihin; Jumanah Jumanah; Arif Nugroho; Yuni Dwi Cahyani; Ikhda Ratri Auladatisyifa; Riyan Herdiana (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
The Covid-19 outbreak emerged in early 2020, crippling global economic activities, including the tourism sector in Indonesia. The decline in the number of tourists visiting Indonesia had a significant impact on the country's economy. It is a significant responsibility for the government to formulate policies for the post-pandemic development of tourism in Indonesia. One of the policies for the development of the tourism sector is the concept of the